Safety Considerations and Fire Prevention along the Transportation Chain of Electric Vehicles - Stüber, Samuel; Peters, Andreas (My University, 2024)
From a seafarer’s perspective, one of the worst things to happen on board a vessel is a fire. Accidents in the recent past involving car carriers transporting electric vehicles have triggered the question of the safety of transporting electric vehicles on ocean-going ships. Thus, this the-sis explores the transportation chain of electric vehicles, involving the handling of electric ve-hicles at each of the steps in the export transportation chain. Additionally, risk factors along the transportation chain in addition to preventive measures are explored at each step. For this, a literature review is combined with a case study in the Gothenburg region. Literature on the fields of the management of batteries, firefighting and handling of electric vehicles, and the general management of the transportation chain is reviewed. The case study involves expert interviews with 12 interviewees from stakeholders along the transportation chain from the man-ufacturer onto the RoRo- or RoPax vessels. In the case study, the suggestions found in published literature are compared with the actual procedures in practice to reveal similarities and differ-ences. It is discovered that the handling of electric vehicles is not materially different from the handling of vehicles with an internal combustion engine. For each step in the transportation chain, individual risk factors are identified, in addition to risk factors affecting the entire trans-portation chain. These are the 12V/24V batteries in the electric vehicles, human error, and a lack of information flow between the various individual stakeholders. Similarly, preventive measures at each step in the transportation chain are identified in addition to overarching pre-ventive measures. A state of charge in the vehicle’s battery of less than 50%, training and edu-cation, and communication between stakeholders are suggested as preventive measures in order to prevent the ignition of the electric vehicles and to make the transportation chain safer.
Keywords: Electric Vehicles; Transport Safety; Fir Prevention; Maritime Transportation; Transportation Chain, Multimodal Transport; Risk Factors; Safety Measures; Battery Safety